Innovative Self-Assessment Service in Public–Private Partnership Infrastructure Development in East Java Province - Wirangga Putra, Gesa; Handoko, Rudy; Ibnu Rochim, Achluddin (Sospol, 2025)
Public–Private Partnership (PPP) has emerged as a key strategy to address infrastructure development challenges in Indonesia. This study focuses on the innovation of the Self-Assessment Service for PPP Projects (SELASAR KPBU), developed by the Bureau of Development Administration of East Java Province, to accelerate infrastructure project preparation. Adopting a descriptive qualitative method, the research collected data through observations and 10 purposively selected interviews with stakeholders from local government agencies and private sector representatives during 2023. The Innovation Lifecycle Theory by the OECD guided the analysis of the innovation process. The findings reveal that SELASAR KPBU significantly improved the efficiency and transparency of project feasibility assessments by digitizing the screening process. This innovation not only aligns with digital governance initiatives but also offers a replicable model for other regional governments aiming to enhance investment facilitation. Practical implications suggest the need for continuous capacity building and broader dissemination of digital public service innovations to maximize their impact.